Klimakrise: Wege aus dem Dilemma - Diekmann, Andreas (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
How can the transformation to a CO2-neutral economy and society still succeed? Based on facts and the state of scientific research, this study analyses the basics of climate policy, climate policy measures and the problems of acceptance of climate policies among the population. These are aimed less at changing individual behaviour and more at creating social structures and institutions that enable environmentally friendly action. The price of CO2, infrastructure, technological innovations and international climate agreements play a key role in this regard. However, it should not be forgotten that climate policy only has a chance if it is supported by the population.